Structural synthesis and modification of zeolite as methane adsorbent - Nor Kamarudin, Khairul Sozana; Mat, Hanapi; Hamdan, Halimaton (2003)
Improvements in the technologies for the synthesis of zeolites and development of zeolite with different pore sizes hold a great promise in the chemical and petrochemical industries. Adsorption of methane in porous materials such as zeolite offers a possibility of storing methane at low pressure with high capacity. In this research, zeolite X (Y) have been hydrothermally synthesized in the laboratory with different composition (6.4Na2O: Al2O3: xSiO: 180H2O, 2 < x <20) followed by characterization procedure using XRD method and BET surface analyser. Post synthesis or modification using cation exchange technique has been carried out to observe the effect different cation (Li, K, Ca, Mg) on zeolite’s properties. Zeolites with faujasite type of framework were produced with different relative crystallinity and surface area. The surface area of exchanged zeolite varied depending on cation types and groups. Molecular simulation was also carried out to determine surface area of zeolites and followed by methane adsorption at 273K and 100kPa. Result shows that cation exchange modification can increase the surface area, hence increase methane adsorption.